DESIGN AND DEVELOPMENT OF A MOBILE GAME-BASED APPLICATION FOR BINARY NUMBER CONVERSION - Ichsan; Munzir Umran; Muhammad Irsyad (Bulletin of Engineering Science, Technology and Industry, 2024)
The topic of binary numbers often poses challenges for students in understanding fundamental concepts of computer science and mathematics. To address this difficulty, this research designs and implements an educational game application based on mobile platforms aimed at facilitating the learning process of binary numbers. The application is developed using Flutter, an open-source framework that enables efficient cross-platform mobile application development. Key features of this application include interactive tutorial modules, exercises for converting binary numbers to decimal and vice versa, and educational games designed to reinforce concept understanding through gamification methods. Additionally, the game features can be shared via email, allowing for enhanced collaboration and feedback among users. Testing results indicate that users experience a significant improvement in their understanding and skills in binary number conversion. Specifically, 87% of users agreed that this application can be effectively used as a practice medium for converting binary, octal, decimal, and hexadecimal number systems. With an intuitive interface and an enjoyable learning approach, this application is expected to become an effective learning aid for students in mastering binary numbers..